Canonisation as Innovation : Anchoring Cultural Formation in the First Millennium BCE - Agut-Labordère, Damien; Versluys, Miguel John (Euhormos: Greco-Roman Studies in Anchoring Innovation, 2022)
Drawing on case-studies from the first millennium BCE, this volume explores canonisation as a form of cultural formation. The book asks why and how canonisation works and thereby investigates the importance of the concept of anchoring to arrive at innovation in particular.